Efeito da fragmentação florestal sobre a estrutura da comunidade de drosofilídeos (Diptera) no extremo sul da Amazônia - SANTOS, Ronildon Miranda dos (Universidade Federal do Pará, 2013)
Ambient disturbances frequently produce changes in the structure of landscape and fauna diversity. Data about degradation's history, ambient structure and species have been collected in 30 forest fragments of different sizes in Alta Floresta and Apiacás towns, south of the Amazonia, to verify how Drosophilidae community answers to forest fragmentation. The results showed great heterogeneity between forest fragments; however diversity was similar between larger and best conserved and small with high degree of degradation. A total of 10.692 individuals of Drosophilidae, divided in 62 taxons, were collected. Relation between forest fragments size and species diversity was not observed. However, e opening of sub-forest was one of ambient variables that contributed the more to reduction of species diversity. Estimate of species richness for the region was around 100. The structure of abundance of communities was more similar between the forest fragments than species composition. About 34% of total richness was restricted to de forest edge and 19% to the center of the remnants; 47% of the species was common to both habitats. Some species of drosophilids answered to a distance gradient forest matrix-center. D. malerkoffiana, S. latifasciaefonnis and Z. indianus decreased their frequencies with the proximity of the center. On the other hand, the group willistoni increased in abundance. The main effect of the forest spalling on the community of drosophílids is the drastic alteration in species composition, with the matrix of the habitat being determinative in species composition of forest fragments.